The Role of β-Arrestin Proteins in Organization of Signaling and Regulation of the AT1 Angiotensin Receptor - Turu, Gábor; Balla, András; Hunyady, László (Frontiers in Endocrinology, 2019)
AT1 angiotensin receptor plays important physiological and pathophysiological roles in the cardiovascular system. Renin-angiotensin system represents a target system for drugs acting at different levels. The main effects of ATR1 stimulation involve activation of Gq proteins and subsequent IP3, DAG and calcium signaling. It has become evident in recent years that besides the well-known G protein pathways, AT1R also activates a parallel signaling pathway through β-arrestins. β-arrestins were originally described as proteins that desensitize G protein-coupled receptors, but they can also mediate receptor internalization and G protein-independent signaling. AT1R is one of the most studied receptors, which was used to unravel the newly recognized β-arrestins mediated pathways. β-arrestin-mediated signaling has become one of the most studied topics in recent years in molecular pharmacology and the modulation of these pathway of the AT1R might offer new therapeutic opportunities in the near future. In this paper, we review the recent advances in the field of β-arrestin signaling of the AT1R, emphasizing its role in cardiovascular regulation and heart failure.